Cloning and functional analysis of expansin TaEXPA9 orthologs in winter wheat in frigid regions - Z.Y. ZHAO; B.Z. HU; X. FENG; F.L. LI; F.M. HE; J.W. WU; C.J. XU; L. LI; Y.Q. XU (Biologia Plantarum, 2022)
Long-term low temperatures restrict the regrowth of winter wheat (Triticum aestivum L.), thus decreasing agricultural output. Non-enzymatic expansins, which are related to plant growth, have been reported to respond to drought, salinity, and low-temperature stress. We obtained an expansin 3 gene, TaEXPA9. It is located in winter wheat cv. Dongnong with high cold hardiness. We analyzed the expression patterns of TaEXPA9-A/B/D in this cultivar and conducted a subcellular localization analysis of TaEXPA9-A/B/D in the onion epidermis. Transgenic Arabidopsis thaliana line with EXPA9-A/B/D overexpression was obtained to examine the effects of the orthologous genes of these expansins on plant growth and low-temperature stress resistance. The results showed that EXPA9-A/B/D expression significantly increased at 4 °C, it was higher in the roots than in shoots, and EXPA9-A/B/D was localized in the cell wall. The roots were well-developed in the transgenic A. thaliana, and the growth-related markers and setting rate were better than in the wild-type. Recovery was stronger in the transgenic plants after freezing stress. At low-temperature stress, the antioxidant enzyme activities and content of osmoregulatory substances in the TaEXPA9-A/B/D-overexpressing A. thaliana plants were significantly higher than in the wild-type plants, and the degree of membrane lipid peroxidation was lower. In summary, TaEXPA9 orthologous genes participate in the low-temperature stress response, and they might be of great importance in molecular breeding.